Management outcomes of canalicular laceration in children - Alhammad, Fatimah; Galindo-Ferreiro, Alicia; Khandekar, Rajiv; Al-Sheikh, Osama; Alzaher, Fatimah; Schellini, Silvana [UNESP] (Wolters Kluwer Medknow Publications, 2020)
PURPOSE: To report the epidemiological data, clinical profile, management, and outcomes of canalicular lacerations in the pediatric age group in a tertiary eye care hospital in Saudi Arabia. METHODS: This retrospective study evaluated pediatric patients who underwent canalicular laceration repair in the last 15years at King Khalid Eye Specialist Hospital (KKESH), Saudi Arabia. Demographics, causes of injury, type of trauma, surgical approach, and outcomes were analyzed. The success of repair was defined as the absence of epiphora after canaliculus repair with negative dye disappearance test (DDT). Success within subgroups was compared. P<0.05 was considered statistically significant. RESULTS: The study sample was comprised of 43 patients, with a median age of 6.35years (range, 1.77-17.96years). Most of the patients were males (69.8%). Sharp objects were the most common cause of canalicular laceration (46.5%), being 9 (20.9 %) caused by a metallic clothing hanger. Lower canaliculus was involved in 65.1%, upper canaliculus in 32.6%, and both canaliculi in 2.3% of patients. Canaliculus repair was performed with a bicanalicular stent in 58.1 % and monocanalicular stent in 41.9 % of patients.The success rate and risk of complications using bicanalicular or monocanalicular stent did not differ (P=0.065). Functional success was achieved in 87.5% of patients. CONCLUSION: Canalicular laceration is common in male children, mainly affecting the lower canaliculus. There was no difference in success rate between monocanalicular and bicanalicular stent. As canalicular laceration could be related to social determinants, the main causes should be highlighted in community health education initiatives.
Keywords: Canalicular; eyelid; laceration; trauma